2014
DOI: 10.1590/s0100-736x2014001100009
|View full text |Cite
|
Sign up to set email alerts
|

Elimination of the tremorgenic toxin of Ipomoea asarifolia by milk

Abstract: RESUMO.-[Eliminação da toxina tremorgênica de INTRODUCTIONIpomoea asarifolia R. et Schult. (common name: salsa), family Convolvulaceae, is a plant native to South and Central America. In Brazil it is very common in the Amazon region, in the Northeast, and along the coast, from northern Brazil to the southern states of Rio de Janeiro and São Paulo (Kissmann & Groth 1992). I. asarifolia is a tremorgenic plant that causes poisoning in sheep (Döbereiner et al. 1960, Guedes et al. 2007), goats (Döbereiner et al. 19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 16 publications
0
7
0
2
Order By: Relevance
“…The toxic principle of F. humboldtiana is unknown, but it is suggested that naftodiantrones may be related to the pathogenesis of tegumentary lesions (Pimentel et al 2007). Other toxins from Brazilian plants can be excreted in milk, such as pyrrolizidine alkaloids, steroidal saponins, monocrotaline, ptaquiloside, and tremogenic toxin from Ipomoea asarifolia (Dickinson et al 1976, James 1994, Medeiros & Górniak 1995, Lemos et al 1998, Lopes et al 2014.Therefore, the possibility of F. humboldtiana toxin(s) being excreted by the milk of poisoned cows should be investigated better, since this characteristic was not observed in previous studies in cows (Knupp et al 2018) and dairy goats (Santos et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The toxic principle of F. humboldtiana is unknown, but it is suggested that naftodiantrones may be related to the pathogenesis of tegumentary lesions (Pimentel et al 2007). Other toxins from Brazilian plants can be excreted in milk, such as pyrrolizidine alkaloids, steroidal saponins, monocrotaline, ptaquiloside, and tremogenic toxin from Ipomoea asarifolia (Dickinson et al 1976, James 1994, Medeiros & Górniak 1995, Lemos et al 1998, Lopes et al 2014.Therefore, the possibility of F. humboldtiana toxin(s) being excreted by the milk of poisoned cows should be investigated better, since this characteristic was not observed in previous studies in cows (Knupp et al 2018) and dairy goats (Santos et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…It has already been demonstrated that other plants in the semi-arid region also have phytotoxins eliminated in milk, causing poisoning of offspring that ingest it. Using mice as an experimental model, Lopes et al (2014) demonstrated that the tremorgenic toxin present in Ipomoea asarifolia, or its metabolite, is eliminated in the milk of females that consume ration containing this plant, causing tremors and even the death of the offspring. Posteriorly, Carvalho de Lucena et al (2014) also confirmed the occurrence of poisoning in lambs that ingested milk from ewes that fed exclusively on I. asarifolia.…”
Section: Discussionmentioning
confidence: 99%
“…Outras toxinas que podem ser eliminadas pelo leite são os alcalóides pirrolizidínicos (Dickinson et al 1976), as saponinas esteroidais (Lemos et al 1998), as monocrotalinas (Medeiros & Górniak 1995, Medeiros et al 1998, 1999 e o ptaquilosídeo, que é o princípio ativo de Pteridium aquilinum (James 1994). Além destes compostos, a toxina tremorgênica da Ipomoea asarifolia também é excretada pelo leite (James 1994, Lopes et al 2014.…”
Section: Discussionunclassified